Statistical assessment of the activity of collective accommodation facilities and their contribution to the economy of the Russian Federation regions - V. N. Salin; M. V. Vakhrameeva; V. V. Narbut (Статистика и экономика)
The purpose of the study. Tourism is a priority area of economic development. Short-term accommodation of tourists plays an important role in the tourism industry. The indicator of the number of persons placed in collective accommodation facilities is used to determine the tourist flow in the context of the regions of the Russian Federation. The approach we have used in this study aims to analyze the activity of collective accommodation facilities and assess their contributionto the economy of the Russian Federation regions based on current statistical information. The research was carried out at the expense of budgetary funds on the state assignment to the Financial University under the Government of the Russian Federation. The study focuses on:analysis of the activity of collective accommodation facilities on the territory of Russia,testing the hypothesis that the differences in the main indicators, characterizing the activity of collective accommodation facilities are due to the influence of the territorial factor,evaluate the efficiency of functioning of collective accommodation facilities and their profitability, and highlight the regions of Russia with low, medium and high levels of profitability of tourist accommodation facilities,assess the contribution of the activity of collective accommodation facilities for tourists to the economy of the regions of Russia. Materials and methods. In the paper, the authors considered definitions, classification, a system of indicators that form a methodological basis for statistical observation of the activity of collective accommodation facilities and their presentation in accordance with the current international and national statistical standards. We applied the grouping method, structural and dynamic data analysis. The hypothesis of the normal distribution of the data was tested on the basis of the Shapiro-Wilk Test. The hypothesis that the differences in indicators characterizing tourist activity are due to the influence of the regional factor was tested using the nonparametric Kruskal-Wallis Test. To assess the contribution of the activity of collective accommodation facilities to the economy of the Russian region, the authors calculated an integral index assessing the resources and results of tourism activities in the region. The analysis was carried out according to 5 indicators characterizing tourist activity in 82 regions of the Russian Federation in 2019.Results. The study found that the territorial factor has a statistically significant effect on the number of seats for receiving tourists, the number of accommodated persons, the number of overnight stays. At the same time, the differences in the distribution of the collective accommodation facilities over the territory of Russia are caused not by the belonging of the region of Russia to a certain federal district, but by other factors. The study also made it possible to come to the conclusion that, in terms of the profitability of collective accommodation facilities, the regions of Russia are extremely heterogeneous. The authors identified groups of Russian regions with profitability of collective accommodation facilities below average, above average and high. The integral index, based on the resources and results of tourist activity, made it possible to determine the regions of Russia, in which the results of tourist activities are ahead, correspond or lag behind the available resources for the implementation of tourist activities. Conclusion. The results obtained will make it possible to correlate the resources of each Russian region for the implementation of tourist activities with its results. An increase in the number of accommodations, an increase in their level of comfort, accessibility, and convenient location will give an impetus to the development of the tourism sector in Russia; arouse interest in tourist trips both among citizens of the country and among foreign guests. The regional aspect of the location of accommodation facilities is extremely important, since it is not only the basic position of the tourist infrastructure, but also has a direct impact on the contribution of tourist activity to the economy of the region of Russia. Therefore, the issue of the influence of accommodation facilities on the region’s economy requires further study.